Teaching Grammar in anEnglish as a Foreign Language (Efl) Context - Garrett, Lisa (The Australian Journal of Indigenous Education, 2003)
Abstract This paper is based on my recent experiences as a classroom teacher in Coconut Island State School on Poruma (Coconut Island), a Torres Strait primary school, and discusses best practice in explicitly instructing Islander students in Standard Australian English grammar. I argue for a variety of approaches, informed by a careful consideration of the students’ cultural understandings and their language needs. These are crucial for determining which grammatical approach is most effective in ensuring effective independent second language acquisition in Standard Australian English.